Novel Omega-Gate heterojunction tunneling FET with a new analytical model. (7th May 2021) - Qing, Yihong; Chiang, Te-Kuang; Wang, Lin; Du, Feibo; Xie, Tiantian; Cao, Yirui; Liu, Zhiwei
Abstract: In this paper, a novel Omega-Gate heterojunction tunneling field effect transistor (HTFET) is proposed by decreasing the gate coverage of gate-all-around (GAA) HTFET. Compared with GAA HTFET, Omega-Gate HTFET maximizes the electrostatic gate control while minimizing the device area, and it has a smaller natural length, not scarifying the high driving capability. A new analytical model is proposed for Omega-Gate HTFET. By introducing an overlap coefficient of η that is based on the Omega-Gate structure, the natural length can be calibrated more accurately. I–V characteristics can be obtained by using the PPA method and tunneling mechanism equations. The model can be verified by Technology Computer Aided Design (TCAD) simulations applying G a A s 0.5 S b 0.5 / I n 0.53 G a 0.47 A s Omega-Gate HTFET. It is shown that the tunneling rate of Omega-Gate HTFET is five times that of tri-gate HTFET, its natural length can be scaled down a maximum of 38%, and it has an excellent drive capability compared with GAA HTFET.